Serum RANKL levels and bioelectric impedance assessments in knee osteoarthritis patients - Pala, Elif; Denkçeken, Tuba; Turgay, Türkan (Journal of Surgery and Medicine, 2020)
Aim: Osteoarthritis (OA) is a common joint disease that is caused by mechanical, genetic, and biochemical factors, and knee OA is one of the reasons of mobility limitation and disability. The receptor activator of NF-κB ligand (RANKL) is directly involved in the differentiation of osteoclasts through its receptor RANK. In this study, we aimed to study circulating serum levels of RANKL, and assess knee bioelectric impedance in control and patients with knee OA. Methods: In this case-control study, OA severity was evaluated by the Kellgren–Lawrence grading scale, based on which we categorized patient groups. There were 22 control individuals (Grades 0 and 1), 11 early (Grade 2) and 30 late OA patients (Grades 3 and 4). We evaluated the performance of the bioimpedance phase angle values at 50 kHz. The RANKL protein levels in the serum were quantified using Enzyme-Linked Immunosorbent Assay (ELISA). Results: It was observed that the control group could not be differentiated from the study group by using phase angle values (P=0.925). Concerning the RANKL levels, although it shows a relative increase in the study group, it did not reach a significant level (P=0.116). Conclusion: The phase angle values at 50 kHz and RANKL levels may not be used in predictive detection of knee OA. Additional studies with larger sample sizes are needed to interpret if these changes are consistent and clinically related.